Phytochemical profiling, antioxidant activity, cytotoxicity and GC-MS characterization of Ganoderma applanatum - JOEY B. INVENTO; GECELLE MARIE V. BENIDA; JENNY CEL M. TEJANO; JASMIN JOY C. ENOJALES; MARY JOY O. PAGENTE; KAYE CATHERINE R. DOLOGAN; SHEILA MARIE Y. PLIMACO (Nusantara Bioscience, 2026)
Abstract. Invento JB, Benida GMV, Tejano JCM, Enojales JJC, Pagente MJO, Dologan KCR, Plimaco SMY. 2026. Phytochemical profiling, antioxidant activity, cytotoxicity and GC-MS characterization of Ganoderma applanatum. Nusantara Bioscience 18 (1): n180104. https://doi.org/10.13057/nusbiosci/n180104. This study investigated the medicinal potential of Ganoderma applanatum ethanolic extracts by focusing on antioxidant capacity, cytotoxicity, and bioactive compound profiling. Samples were collected, authenticated, and subjected to phytochemical screening, revealing the presence of flavonoids, steroids, saponins, tannins, and alkaloids. The free-radical scavenging ability of the extracts was determined using a modified DPPH assay, where dilutions (10-1,000 µg/mL) were mixed with 0.1 mM ethanolic DPPH, vortexed, incubated in the dark for 1 h at room temperature, and absorbance read at 517 nm in triplicates to calculate % inhibition and IC50. The extract demonstrated a 97% inhibition at 500 µg/mL, indicating strong free radical neutralization. GC-MS analysis identified 26 bioactive compounds, including fatty acids, hydrocarbons, phenolics, terpenoids, and steroids, many of which are associated with antioxidant and cytotoxic effects. Cytotoxicity was evaluated via the Brine Shrimp Lethality Test (BSLT) by the MSU-IIT Chemistry Department, exposing 10 Artemia salina nauplii per replicate to triplicate dilutions (1-10,000 μg/mL) for 24 h, and calculating % mortality. LC50 values were determined to be 37 µg/mL, signifying potent toxicity. These results collectively highlight G. applanatum’s rich phytochemical composition and significant bioactivities, supporting its traditional medicinal use. The evidence-based findings suggest that the ethanolic extract possesses promising antioxidant and cytotoxic properties, warranting further investigation for therapeutic applications.